Analisis Keamanan Sistem Informasi Berbasis Website Dengan Metode Open Web Application Security Project (OWASP) Versi 4: Systematic Review - Anggi Elanda; Robby Lintang Buana (Universitas Negeri Medan, 2020)
Abstract – OWASP (Open Web Application Security Project) version 4 issued by a non-profit organization called owasp.org which is dedicated to the security of web-based applications. This systematic review is intended to review whether the Open Web Application Security Project (OWASP) method is widely used to detect security in a website-based Information System. In this systematic review, we review 3 literature from several publisher sources and make a comparison regarding OWASP version 4 results and the security level of a web server from the publisher's source.Keywords— OWASP, Website Vulnerability, Website Security Detection